Optimasi sediaan salep minyak cengkeh (syzigium aromaticum) dalam basis larut air - Rani Prabandari (Universitas Harapan Bangsa Purwokerto, 2018)
Abstract The clove flower essential oil (Syzygium aromaticum) with the active compound eugenol has been widely investigated and is known to be efficacious as an anti-inflammatory agent, and further research on its formulation continues. The formula developed in this study was a topical ointment dosage form using a water soluble base (oleic acid enhancer and propylene glycol). This study aims to determine the physical and irritant properties of the clove flower essential oil ointment (MABC) if a hydrocarbon base is used. The ointment is made by the smelting method with a concentration of 5% (F1), 10% (FII) and 15% (FIII). The ointments of the three formulas were then evaluated for their physical properties, including dispersion, adhesion and pH. The results of statistical tests with the LSD test showed that there were significant differences between formulas. The higher the concentration of MABC, the greater the spread (p0.05). The results of the Simplex Lattice Design irritation test also show that water-soluble base ointment with a concentration of 5%, 10% and 15% MABC does not cause an irritating effect. Keywords: Syzygium aromaticum, base of water soluble ointment, anti-inflammatory.